Make Investment Scaling-Up Work in Benin : A Macro-Fiscal Analysis - Barhoumi, Karim; Cui, Larry; Dieterich, Christine; End, Nicolas (Washington, D.C. : International Monetary Fund, 2016)
This paper conducts a systematic growth and fiscal analysis to determine: (1) the growth potential of Benin's ambitious scaling-up of investment, and (2) how the government can generate the necessary fiscal space needed to increase investment without jeopardizing Benin's solid macroeconomic performance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet